Upaya Peningkatan Kualitas Penangkapan Ikan Dengan Pendekatan Traceability Di Desa Seraya Timur, Kabupaten Karangasem, Provinsi Bali - Purba, Ravena Krisdayanti; Dharma, I Gusti Bagus Sila; Puspitha, Ni Luh Putu Ria (Journal of Marine Research and Technology, 2025)
Efforts to improve fishing quality refer to various strategies and actions to enhance the yield, efficiency, and sustainability. The main objective of this study was to analyze the fishing practices, including the fishing gear, methods, and catch results used, and to identify the efforts made to improve fishing quality in Seraya Timur Village, Karangasem Regency. The research was conducted in March 2024, using observational methods and interviews with fishermen. The sampling technique used was purposive sampling. The results indicate that fishermen in Seraya Timur Village use environmentally friendly fishing gear, specifically Drift Gillnets, with the main catch being skipjack tuna. The priority strategy that needs to be implemented in Seraya Timur Village is the WO (Weakness-Opportunity) strategy. It is suggested that training, technology, and infrastructure are key to improving fishing quality and ensuring the sustainability of fisheries resources in Seraya Timur Village.